High numbers of PDCD1 (PD-1)-positive T cells and B2M mutations in microsatellite-unstable colorectal cancer. (1st February 2018) - Janikovits, Jonas; Müller, Meike; Krzykalla, Julia; Körner, Sandrina; Echterdiek, Fabian; Lahrmann, Bernd; Grabe, Niels; Schneider, Martin; Benner, Axel; Doeberitz, Magnus von Knebel; Kloor, Matthias
ABSTRACT: DNA mismatch repair (MMR)-deficient cancers accumulate high numbers of coding microsatellite mutations, which lead to the generation of highly immunogenic frameshift peptide (FSP) neoantigens. MMR-deficient cells can grow out to clinically manifest cancers either if they evade immune cell attack or if local T-cells get exhausted. Therefore, a subset of MSI cancer patients responds particularly well to treatment with immune checkpoint inhibitors. We analyzed whether immune evasion in MMR-deficient cancer mediated by loss of HLA class I or II antigens is related to local immune cell activation status. Microsatellites located in Beta2-microglobulin (B2M) and the HLA class II-regulatory genes RFX5 and CIITA were analyzed for mutations in MMR-deficient colorectal cancers (n = 53). The results were related to CD3-positive and PDCD1 (PD-1)-positive T-cell infiltration. PDCD1 (PD-1)-positive T-cell counts were significantly higher in B2M -mutant compared to B2M -wild type tumors (median: 22.2 cells per 0.25 mm 2 vs. 2.0 cells per 0.25 mm 2, Wilcoxon test p = 0.002). Increasing PDCD1 (PD-1)-positive T-cell infiltration was significantly related to an increased likelihood of B2M mutations (OR = 1.81). HLA class II antigen expression status was significantly associated with enhanced overall T-cell infiltration, but not related to PDCD1 (PD-1)-positive T-cells. These results suggest that immune evasion mediated by B2M mutation-induced loss of HLA class I antigen expression predominantly occurs in an environment of activated PDCD1 (PD-1)-positive T cell infiltration. If B2M mutations interfere with anti-PDCD1 (PD-1)/CD274 (PD-L1) therapy success, we predict that resistance towards anti-PDCD1 (PD-1) therapy may – counterintuitively – be particularly common in patients with MMR-deficient cancers that show high PDCD1 (PD-1)-positive T cell infiltration.